Comparison of Safety of Low Osmolar vs Iso-osmolar Contrast Media for Prevention of CIN in Patients Undergoing Coronary Intervention - Khan, Mahmud Hossain; Amin, Md Al; Khaled, Md Fakhrul Islam; Asaduzzaman, Md; Islam, Md Nazrul; Ataullah, Md; Deeba, Shahjadi Farah; Dina, Sirajam Munira; Kulsum, Umme; Mahmood, Manzoor (University Heart Journal, 2025)
Background: Contrast-induced nephropathy (CIN) is a significant complication following coronary angiography (CAG) and percutaneous coronary intervention (PCI), leading to worsened renal function, prolonged hospital stays and increased healthcare costs. The choice of contrast media used during these procedures play vital role in development of CIN. Objective: To compare the effectiveness of low osmolar contrast media (LOCM) and iso-osmolar contrast media (IOCM) in reducing the incidence of CIN in patients undergoing CAG or PCI. Methods: In this prospective observational study, 60 patients undergoing CAG or PCI were randomized equally into IOCM (n=30) or LOCM (n=30). Serum creatinine (Scr) level and estimated glomerular filtration rate (eGFR) were measured at baseline and 72 hours post-procedure. CIN was defined as a >25% or >0.5 mg/dL increase in Serum creatinine. Logistic regression models were used to identify predictors of CIN Results: CIN incidence was higher in LOCM group (33.3%) than IOCM group (10%) (p=0.03). LOCM usage significantly increased in Scr (p=0.001) and reduced eGFR (p=0.001), whereas IOCM maintained stable eGFR level (p=0.129) and Scr (p=0.023). Diabetes mellitus (OR 13.88, p=0.034), use of LOCM (OR 10.95, p=0.032), and higher contrast volume (OR 1.17, p=0.012) were identified independent predictors of CIN. Conclusion: IOCM was associated with significantly lower CIN risk and more stable renal function compared to LOCM. Considering these findings, IOCM should be preferred in high-risk patients, especially those with diabetes or requiring larger contrast volumes, to minimize the risk of CIN. Abbreviations: CI-AKI = contrast-induced acute kidney injury, CIN = contrast-induced nephropathy, CM = contrast media, eGFR = estimated glomerular filtration rate, LOCM = low-osmolar contrast medium, AR = attributable risk, OR = odds ratio, CAG = coronary angiography, PCI = percutaneous coronary intervention, Scr = serum creatinine, DM = Diabetes mellitus. CKD = chronic kidney disease University Heart Journal 2025; 21(2): 87-91